2011
DOI: 10.5188/ijsmer.18.18
|View full text |Cite
|
Sign up to set email alerts
|

Step Synthesis Method for Diamond Films on Tungsten Carbide Substrate Surface by Combustion Flame

Abstract: A combustion flame method enables the synthesis of diamond using acetylene-oxygen gas (C 2 H 2 /O 2 ) combustion flame in ambient air. Recently, tungsten carbide (WC) is used as cutting tools in the machining industry. In this study, diamond films were synthesized by combustion flame on WC surfaces. However, it was difficult to synthesize the diamond films on the WC substrate surfaces. Therefore, in order to synthesize the diamond film, a two-step synthesis method was proposed. In this method, the film surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…During the synthesis, the diamond film synthesis and delamination were affected when the distance was altered, because there was a change in the acetylene feather area. We confirmed that delamination at d = 7.0 mm during diamond film synthesis could be effectively prevented [14][15][16]. Therefore, diamond films were synthesized at d = 7.0 mm.…”
Section: Synthesis Conditionssupporting
confidence: 69%
See 4 more Smart Citations
“…During the synthesis, the diamond film synthesis and delamination were affected when the distance was altered, because there was a change in the acetylene feather area. We confirmed that delamination at d = 7.0 mm during diamond film synthesis could be effectively prevented [14][15][16]. Therefore, diamond films were synthesized at d = 7.0 mm.…”
Section: Synthesis Conditionssupporting
confidence: 69%
“…The synthesis conditions are listed in Table 1. These conditions have been determined and reported previously [14][15][16], and are believed to be the optimum conditions for preventing delamination during the synthesis of diamond films. The ratio of the oxygen flow rate (F o = 63.8 cm 3 /s) to acetylene flow rate (F a = 70.9 cm 3 /s) was set to R f = F o /F a = 0.90, because delamination-free crystallite growth could be realized at R f = 0.90 [14][15][16].…”
Section: Synthesis Conditionsmentioning
confidence: 90%
See 3 more Smart Citations